Digital Literacy for Researchers: A Necessity in Today's Digital Age - Jha, Jay Prakash (Journal of Karnali Academy of Health Sciences, 2024)
Digital literacy is essential for medical professionals to effectively utilize computer tools in research and practice. This editorial article highlights the necessity of computer skills for managing manuscripts, adhering to guidelines, and enhancing research visibility. It advocates for techno-literacy training to overcome challenges in digital publishing and ensure efficient dissemination of valuable research findings, ultimately advancing medical knowledge and patient care.